Null Controllability of Hilfer Fractional Stochastic Differential Inclusions - Hamdy M. Ahmed; Mahmoud M. El-Borai; Wagdy El-Sayed; Alaa Elbadrawi (Fractal and Fractional, 2022)
This paper gives the null controllability for nonlocal stochastic differential inclusion with the Hilfer fractional derivative and Clarke subdifferential. Sufficient conditions for null controllability of nonlocal Hilfer fractional stochastic differential inclusion are established by using the fixed-point approach with the proof that the corresponding linear system is controllable. Finally, the theoretical results are verified with an example.